Marginal Zone Lymphoma Complicated by Protein Losing Enteropathy - Stanek, Nadine; Bauerfeind, Peter; Herzog, Guido; Heinrich, Henriette; Sauter, Matthias; Lenggenhager, Daniela; Reiner, Cäcilia; Manz, Markus G.; Goede, Jeroen S.; Misselwitz, Benjamin (Case Reports in Hematology, 2016)
Protein losing enteropathy (PLE) refers to excessive intestinal protein loss, resulting in hypoalbuminemia. Underlying pathologies include conditions leading to either reduced intestinal barrier or lymphatic congestion. We describe the case of a patient with long-lasting diffuse abdominal problems and PLE. Repetitive endoscopies were normal with only minimal lymphangiectasia in biopsies. Further evaluations revealed an indolent marginal zone lymphoma with minor bone marrow infiltration. Monotherapy with rituximab decreased bone marrow infiltration of the lymphoma but did not relieve PLE. Additional treatments with steroids, octreotide, a diet devoid of long-chain fatty-acids, and parenteral nutrition did not prevent further clinical deterioration with marked weight loss (23 kg), further reduction in albumin concentrations (nadir 8 g/L), and a pronounced drop in performance status. Finally, immunochemotherapy with rituximab and bendamustine resulted in hematological remission and remarkable clinical improvement. 18 months after therapy the patient remains free of gastrointestinal complaints and has regained his body weight with normal albumin levels. We demonstrate a case of PLE secondary to indolent marginal zone lymphoma. No intestinal pathologies were detected, contrasting a severe and almost lethal clinical course. Immunochemotherapy relieved lymphoma and PLE, suggesting that a high suspicion of lymphoma is warranted in otherwise unexplained cases of PLE.